A Review of Research on the Influence of Short Video Implanted Ads on Consumers’ Purchase Intention - Wu, Xiaotong (International Journal of Global Economics and Management, 2024)
The short video industry accounts for a prominent proportion of the advertising medium, and with the development of the Internet, short video implanted advertisements have gradually become an important factor influencing consumers’ purchasing behavior. The role of short video implantable ads has also attracted more and more attention in the study of influencing consumers’ purchase intention. To this end, short video implantable ads and their related concepts and characteristics are sorted out, and then the influence of four factors, namely, implantable ads, audience, short video content and short video bloggers, on consumers’ purchase intention is analyzed, and the deficiencies of the existing research and the direction of future research are pointed out.